Field measurements of the backscattering coefficient in a cascading reservoir system: First results from Nova Avanhandava and Barra Bonita Reservoirs (São Paulo, Brazil) - Alcântara, Enner [UNESP]; Watanabe, Fernanda [UNESP]; Rodrigues, Thanan [UNESP]; Bernardo, Nariane [UNESP]; Rotta, Luiz [UNESP]; Carmo, Alisson [UNESP]; Curtarelli, Marcelo; Imai, Nilton [UNESP] (Taylor & Francis, 2016)
In this study, a data set of total suspended matter (TSM), chlorophyll-a (Chl-a), total backscattering coefficient (bb) and the remote sensing reflectance (Rrs) were measured in the euphotic zone of two hydroelectric reservoirs at 71 stations during field surveys in the wet and dry seasons. These two reservoirs are located in a cascading system in Tietê River, São Paulo State, Brazil. The limnological and optical data were interpolated using the ordinary kriging technique to map their spatial distribution. The differences in TSM, Chl-a and in bb in space and time were investigated. The profiling data from bb were analysed. All these data were used to explain the resulting Rrs spectra in these two reservoirs. For both reservoirs, the inorganic fraction of TSM was responsible for the bb variability and therefore modulates the Rrs spectra. The seasonally difference in the optical data will help to understand how the inherent optical properties and the apparent optical properties changes in a cascading reservoir system.